Mozaik srečanj s prof. dr. Francem Bizjakom - Kozinc, Darinka (Les (Ljubljana), 2026)
Darinka Kozinc, M.Sc., professor and long-time principal of the Secondary School of Woodworking in Nova Gorica, shares her personal and professional memories of Prof. Dr Franc Bizjak, her fellow resident and an active member of the community in Solkan near Nova Gorica, as well as a respected and dedicated expert and supporter of education in the Gorica region. Professor Franc Bizjak's legacy is significant and demonstrates that he was a person of integrity, an outstanding teacher, professional, colleague, and connector.
Keywords: Bizjak, Franc; economics; ekonomika; lesarstvo; wood science and technology